Crystal structure of 4-[(3-methoxyphenyl)carbamoyl]butanoic acid, C12H15NO4 - Muhammad, Sirajuddin; Hanifa, B.; Sharif, Ulah; Lo, Kong Mun *; Tiekink, Edward R. T. * (De Gruyter Open, 2020)
C12H15NO4, triclinic, P1̄ (no. 2), a = 5.0167(2) Å, b = 7.9264(5) Å, c = 15.2073(7) Å, α = 98.909(4)°, β = 92.060(4)°, γ = 101.800(4)°, V = 583.36(5) Å3, Z = 2, Rgt(F) = 0.0403, wRref(F2) = 0.1179, T = 293(2) K.